Growth and Yield Performance of Different Mustard Varieties Grown in Barind Tract Soils of Bangladesh - Mehedi Hashan Sohel; Md. Fahad Ali; Ali Ahmed; Md. Raduon Ahmed; Tonima Tasmim; Hadia Akhter; Rahman, Md. Mahabubur (Journal of Tropical Crop Science, 2024)
The present research was conducted to investigate the growth and yield performance of thirteen mustard varieties grown in Chapai Nawabganj district, Bangladesh. Thirteen mustard varieties, viz. “BINA Sarisha-4”, “BINA Sarisha-7”, “BINA Sarisha-9”, “BINA Sarisha-10”, “BARI Sarisha-14”, “BARI Sarisha-15”, “BARI Sarisha-16”, “BARI Sarisha-17”, “BARI Sarisha-18”, an “Indian tall” variety, “Indian short” variety, a Japanese variety “Sarisha” and a local variety were cultivated during “Rabi” (rainy) season 2021-2022. The preparation of land with recommended fertilizer doses, the experiment was arranged in a randomized complete block design consisting of three replications. All the growth, yield, and yield attributes significantly differed among the mustard varieties. In growth attributes, the highest value in plant height (149.97 cm), number of leaves per plant (16.77), leaf length (12.33 cm), number of branches per plant (11.40), and tap root length (22.53 cm) for “Indian tall” variety, “Indian short” variety , “BARI Sarisha-18”, “BINA Sarisha-7”, and “Japanese Sarisha”, respectively. In terms of yield and yield attributes, number of siliqua per plant (102.00), siliqua length (6.37 cm), number of grains per siliqua  (39.50), grain yield per plot (576.33), 1000-seeds weight (3.75 g), biological yield (5.06 ton.ha-1), and harvest index (35.23%) was highest in the “Indian tall” variety , “BARI Sarisha-14”, “BARI Sarisha-14”, “BINA Sarisha-9”, and “Indian short” variety , respectively. The maximum benefit cost ratio (BCR) was 2.21, observed in “BINA Sarisha-9”. Besides, BCR 1.71 and 1.66 were for “BARI Sarisha-14” and “Japanese Sarisha”, respectively. The findings of the study suggested that “BINA Sarisha-9”, “BARI Sarisha-14”, and “Japanese Sarisha” would be suitable for better productivity and recommended for cultivation in the medium highland of Chapai Nawabganj district of Bangladesh.